Lapan aspek Meyppattiyal dalam sajak moden Arivumathi - Sugunadevi Veeran (2021)
This study aims to identify the Meyppattiyal elements found in Arivumathis poems, examine the similarities and evaluate the differences of Meyppattiyal situations found in Arivumathis poems and feelings articulated in Tholkaapiyams work. The study was conducted using qualitative methods including textual analysis, and library research. The data obtained were then analyzed using quantitative, qualitative and explained using deductive, inductive and comparative methods. The explanation is given based on the theory of Meyppatu put forward by Tholkappiyar. A total of 575 poems from 13 books of modern poetry published between 1977 to 2015 were used as research sources. The findings of this study show that modern Arivumathi poetry has eight aspects of Meyppatu namely nakai (laughter), alukai (crying), ilivaral (shame), marutkai (admiration), accam (fear), perumitam (pride), vekuli (anger) and makilcchi (joy) as expressed in Tholkaapiyam. The results also show that not all Meyppatu situations are found in Arivumathi poems. A total of 141 poems reflect aspects of Marutkai. Meanwhile, only 14 poems touch on the Accam aspect. The findings of the study also show that the passage of time, the experience of the poet and the situation of the surrounding society caused some of the Meyppatu situations highlighted by Tholkappiyar to be less relevant and not in line with the situation of modern Arivumathi poetry. In conclusion, this study proves the instincts of the feelings of the present generation manifest the Meyppatu aspect. The implications of this study show that the Meyppatu aspect can be used in understanding human psychology and providing solutions to any problems that exist in the community.